Inhaled delivery of a lipid nanoparticle encapsulated messenger RNA encoding a ciliary protein for the treatment of primary ciliary dyskinesia. (August 2022) - Woo, Caroline J.; Allawzi, Ayed; Clark, Nicholas; Kaushal, Neha; Efthymiou, Tim; Thamsen, Maike; Nguyen, Jane; Wooster, Richard; Sullivan, James C.
Abstract: Primary ciliary dyskinesia (PCD) is a respiratory disease caused by dysfunction of the cilia with currently no approved treatments. This predominantly autosomal recessive disease is caused by mutations in any one of over 50 genes involved in cilia function; DNAI1 is one of the more frequently mutated genes, accounting for approximately 5–10% of diagnosed PCD cases. A codon-optimized mRNA encoding DNAI1 and encapsulated in a lipid nanoparticle (LNP) was administered to mice via aerosolized inhalation resulting in the expression human DNAI1 in the multiciliated cells of the pseudostratified columnar epithelia. The spatial localization of DNAI1 expression in the bronchioles indicate that delivery of the DNAI1 mRNA transpires the lower airways. In a PCD disease model, exposure to the LNP-encapsulated DNAI1 mRNA resulted in increased ciliary beat frequency using high speed videomicroscopy showing the potential for an mRNA therapeutic to correct cilia function in patients with PCD due to DNAI1 mutations.